2020
DOI: 10.1038/s41379-020-0580-6
|View full text |Cite
|
Sign up to set email alerts
|

Myxoinflammatory fibroblastic sarcoma: an immunohistochemical and molecular genetic study of 73 cases

Abstract: Myxoinflammatory fibroblastic sarcoma (MIFS) is a rare, low-grade soft tissue neoplasm preferentially arising in the extremities of young to middle-aged adults that is characterized histologically by a variegated appearance and absence of a distinctive immunophenotype. Herein a series of 80 cases of MIFS has been evaluated to define potential features and markers that may facilitate diagnosis. An immunohistochemical study with a large panel of antibodies showed strong positivity of the tumor cells for bcl-1 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 41 publications
0
45
0
5
Order By: Relevance
“…While its physiologic role is uncertain, it appears to promote cell proliferation through activation of the Hippo pathway ( 23 ); interestingly, it has been suggested to have a role in nerve formation and neural crest migration ( 24 ). Amplification has been reported in myxoinflammatory fibroblastic sarcoma ( 14 , 25 , 26 ), along with several other sarcomas ( 27 ); however, to our knowledge, fusion genes involving VGLL3 have not previously been reported. The precise role of members of the chromodomain helicase DNA-binding (CHD) protein family, including CHD7/9, are also unclear ( 28 ).…”
Section: Discussionmentioning
confidence: 70%
“…While its physiologic role is uncertain, it appears to promote cell proliferation through activation of the Hippo pathway ( 23 ); interestingly, it has been suggested to have a role in nerve formation and neural crest migration ( 24 ). Amplification has been reported in myxoinflammatory fibroblastic sarcoma ( 14 , 25 , 26 ), along with several other sarcomas ( 27 ); however, to our knowledge, fusion genes involving VGLL3 have not previously been reported. The precise role of members of the chromodomain helicase DNA-binding (CHD) protein family, including CHD7/9, are also unclear ( 28 ).…”
Section: Discussionmentioning
confidence: 70%
“…Immunohistochemistry has been widely used in MIFS, but no specific immunophenotype has been found. However, differential responsiveness to the various markers has been observed in the previous studies, including Vimentin, D2-40, CD68, bcl-1, CD10, and CD163 ( 3 , 12 ). In the present study, we found consistent and strong immunoreactivity for Vimentin and CD10 in the tumor cells in this case.…”
Section: Discussionmentioning
confidence: 77%
“…In the mucus background, the tumor spindle cells and epithelioid cells are usually connected to each other to form a complex network structure, and a large number of the neutrophils, macrophages, and plasma cells can be seen, but the mitotic figures and necrosis are not commonly observed in this tumor. Immunohistochemistry has been found to play a very limited role in the diagnosis of MIFS because it has no specific tumor markers ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that VGLL3 can activate the Hippo pathway and cellular proliferation through the inhibition of the YAP/TAZ axis in lung and breast carcinomas 25. Moreover, genomic amplification spanning the locus of VGLL3 has been reported in a subset of soft tissue sarcomas, including myxofibrosarcomas, myxoinflammatory fibroblastic sarcomas, and hemosiderotic fibrolipomatous tumors 26–29. More rarely, VGLL3 can also act as a tumor suppressor gene in cancers such as ovarian carcinomas which harbor recurrent genomic deletions of VGLL3 30.…”
Section: Discussionmentioning
confidence: 99%